Dietary Reference Intake and Nutritional Yield of Lentils in the Northern Great Plains. Issue 3 (1st May 2018) - Graham, Christopher; Beck, R.; Thavarajah, D.
Abstract : Micronutrient deficiencies remain unacceptably high in the diets of many impoverished communities in both developed and developing countries. However, despite declining consumption patterns, pulse crops such as lentils ( Lens culinaris Medik.) can serve as important crops to fill the micronutrient gap. In the present study, three lentil cultivars grown over a 2‐yr study period at two locations (Bison and Wall, SD) in the Northern Great Plains were evaluated to assess the crop's ability to meet the daily nutritional requirements of critical micronutrients: Fe, Mg, K, Se, and Zn. Results were found to vary significantly by location and by cultivar. The greatest differences were found for Se. Between cultivars, concentrations ranged from 115 to 210% of daily requirements per 100 g lentils at Bison and 295 to 381% at Wall. On the basis of average yields per hectare and nutrient concentrations, lentils were found on average to meet the yearly recommended intake requirements of 13 and 20 adult females for Fe, 9 and 13 adults for Mg, 7 and 11 adults for K, 49 and 125 adults for Se, and 14 and 26 adults for Zn between the two study sites, respectively.